Tris(trimethylsilyl) Phosphite (TMSPi) and Triethyl Phosphite (TEPi) as Electrolyte Additives for Lithium Ion Batteries: Mechanistic Insights into Differences during LiNi0.5Mn0.3Co0.2O2-Graphite Full Cell Cycling. Issue 7 (27th May 2017) - Peebles, Cameron; Sahore, Ritu; Gilbert, James A.; Garcia, Juan C.; Tornheim, Adam; Bareño, Javier; Iddir, Hakim; Liao, Chen; Abraham, Daniel P.
Abstract : Tris(trimethylsilyl) phosphite (TMSPi) has emerged as an useful electrolyte additive for lithium ion cells. This work examines the use of TMSPi and a structurally analogous compound, triethyl phosphite (TEPi), in LiNi0.5 Mn0.3 Co0.2 O2 -graphite full cells, containing a (baseline) electrolyte with 1.2 M LiPF6 in EC:EMC (3:7 w/w) and operating between 3.0–4.4 V. Galvanostatic cycling data reveal a measurable difference in capacity fade between the TMSPi and TEPi cells. Furthermore, lower impedance rise is observed for the TMSPi cells, because of the formation of a P- and O-rich surface film on the positive electrode that was revealed by X-ray photoelectron spectroscopy data. Elemental analysis on negative electrodes harvested from cycled cells show lower contents of transition metal (TM) elements for the TMSPi cells than for the baseline and TEPi cells. Our findings indicate that removal of TMS groups from the central P-O core of the TMSPi additive enables formation of the oxide surface film. This film is able to block the generation of reactive TM-oxygen radical species, suppress hydrogen abstraction from the electrolyte solvent, and minimize oxidation reactions at the positive electrode-electrolyte interface. In contrast, oxidation of TEPi does not yield a protective positive electrode film, which results in inferior electrochemical performance.